The chracteristics of active faults and the erosion hazard in coastal-river mouth zones of North Central Vietnam - Hung, Pham Van; Quan, Nguyen Cong (Vietnam Journal of Earth Sciences, 2016)
Based on the integrated analysis of the latest research results allowed to affirm the characteristics and mechanism of activity of the active faults and the relationship with the erosion in coastal-river mouth zones of North Central Vietnam. On the North Central region, the distribution of fault zones with NW-SE, NE-SW, submeridian and subparallel. In particular, the NW-SE fault played a key role in forming the structure plan of area.Under recent geodynamical setting of submeridian compress , the stress field is of strike slip-extensional type, the NW-SE - as normal dextral strike slip, the NE-SW - as normal sinistral strike slip, the submeridian faults is acting as normal strike slip faults. Fault activity and modern movement down local subsidence of the Earth's crust is one of the factors that impact arising erosion in coastal estuaries North Central. Most areas of erosion (in Hai Loc-HauLoc, Hai Thinh-Tinh Gia, Dien Hai, Dien Kim, Dien Thinh-Dien Chau, Canh Duong, Quang Phuc-Quang Trach, Thuan An - Huong Tra and Huong Thuy) with speed and intensity are identical to the tropical coast segment operating fault NW-SE direction cut into the sea, or at the point of intersection of the active fault zone. The more active faults, the more severe coastal erosion.References Nguyễn Văn Cư và Phạm Huy Tiến, 2003: Sạt lở bờ biển miền Trung Việt Nam, Nxb. Khoa học và Kỹ thuật, Hà Nội, 200tr. Lê Xuân Hồng, 1996: Đặc điểm xói lở bờ biển Việt Nam. Luận án Phó tiến sỹ Khoa học Địa lý-Địa chất, Hà Nội. Phạm Văn Hùng, 2006: Đặc điểm hoạt động của các đứt gãy ở khu vực Hồ Kẻ Gỗ-Sông Rác trong Đệ tứ-Hiện đại. Tạp chí Khoa học, số 2A, Đại học Quốc gia Hà Nội, tr.40-50, Hà Nội. Phạm Văn Hùng, 2008: Đặc điểm đứt gãy hoạt động và tai biến xói lở bờ biển Duyên hải Nam Trung Bộ. Tạp chí Các Khoa học về Trái Đất, T.28, 4, tr.314-322. Nguyễn Văn Hùng, 2002: Đặc điểm cơ  bản đứt gãy tân kiến tạo vùng Tây Bắc Việt Nam. Luận án Tiến sỹ Địa chất, Viện Địa chất, Hà Nội. Bùi Văn Thơm, 2002: Đặc điểm đứt gãy tân kiến tạo khu vực Bắc Trung Bộ. Luận án Tiến sỹ Địa chất, Viện Địa chất, Hà Nội. Nguyễn Thế Thôn, Lưu Hải Thống, Lê Đức An, Lại Huy Anh, Nguyễn Thượng Hùng, 1987: Vấn đề chuyển động nâng hạ và nguyên nhân gây xói lở vùng bờ biển Hải Hậu. Tạp chí Các khoa học về Trái Đất, T.9, 3, tr.84-88. Nguyễn Đình Xuyên, Nguyễn Ngọc Thủy, 1997: Tính động đất và độ nguy hiểm động đất trên lãnh thổ Việt Nam. Thành tựu nghiên cứu Vật lý Địa cầu, Nxb. Khoa học và Kỹ thuật, tr.34-91, Hà Nội. Nguyễn Trọng Yêm và nnk, 2006: Nghiên cứu xây dựng bản đồ tai biến môi trường tự nhiên lãnh thổ Việt Nam. Báo cáo tổng kết Đề tài cấp Nhà nước, mã số KC-08-01, lưu trữ Viện Địa chất, Hà Nội.